PLATFORM ECOSYSTEMS OF S&IC IN THE PROCESS OF SELECTING AND IMPLEMENTING TECHNOLOGICAL EQUIPMENT - Alimov, Otabek Sayfutdinovich (THE INNOVATION ECONOMY, 2026)
This article examines the theoretical and practical aspects of applying platform ecosystems to the process of selecting technological equipment for the scientific-industrial centers (S&IC) of New Uzbekistan. It analyzes the essence and multi-level structure of platform ecosystems, the role of digital infrastructure, and open innovation mechanisms. Based on international best practices (Siemens, GE, Bosch, Huawei, Schneider Electric), the study demonstrates the effectiveness of platform-based models for accelerating technological modernization. The article emphasizes the importance of establishing a national platform for equipment selection to support import substitution, localization, R&D development, and technological sovereignty in Uzbekistan.